(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the role and importance of the traditional dishes of the Jizzakh oasis in the stage of gastrotourism development is seen as an example of the traditional dishes of Forish district and its conditions for gastronomic tourism.